The Relationship Between Parental Support and Motivation Students in Participating Scouting Extracurricularies at Sman 1 Koto XI Tarusan - Exandra, Miegel Febri; Wisroni, Wisroni (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the low motivation of students taking part in extracurricular scout activities at SMAN 1 Koto XI Tarusan, because many students violated the rules for completing scout attributes. This research aims to (1) see a picture of parental support for students who are core members of the scout extracurricular (2) see a picture of the motivation of students taking part in scout extracurriculars and (3) find out the relationship between parental support and students' motivation for taking part in scout extracurriculars at SMAN 1 Koto XI Tarusan This research uses a correlational quantitative approach. The population of this research is students who are members of the scout extracurricular core at SMAN 1 Koto The sampling technique in this research was carried out using a stratified random sampling technique. Data collection techniques through questionnaires to research respondents, data analysis techniques using percentages to find correlations using the product moment formula.The research results show that (1) Parental support for students who are members of the scout extracurricular core is still relatively low. (2) Students' motivation to take part in scouting extracurriculars at SMAN 1 Koto XI Tarusan is still relatively low. (3) There is a significant relationship between parental support and students' motivation to take part in scouting extracurriculars at SMAN 1 Koto XI Tarusan. It is recommended for parents to increase good support, and for other researchers to be able to research other variables that can influence student motivation.Keywords : Support, Motivation